Heterogeneous dielectric generalized Born model with a van der Waals term provides improved association energetics of membrane‐embedded transmembrane helices. Issue 16 (4th February 2017) - Dutagaci, Bercem; Sayadi, Maryam; Feig, Michael
Abstract : The heterogeneous dielectric generalized Born (HDGB) implicit membrane formalism is extended by the addition of a van der Waals dispersion term to better describe the nonpolar components of the free energy of solvation. The new model, termed HDGBvdW, improves the energy estimates in the hydrophobic interior of the membrane, where polar and charged species are rarely found and nonpolar interactions become significant. The implicit van der Waals term for the membrane environment extends the model from Gallicchio et al. (J. Comput. Chem. 2004, 25, 479) by combining separate contributions from each of the membrane components. The HDGBvdW model is validated with a series of test cases ranging from membrane insertion and pair association profiles of amino acid side chain analogs and transmembrane helices. Overall, the HDGBvdW model leads to increased agreement with explicit membrane simulation results and experimental data. © 2016 Wiley Periodicals, Inc. Abstract : The implicit membrane model of Heterogeneous Dielectric Generalized Born with a van der Waals term is introduced with an additional dispersion term. The new modification of the model provides a more accurate description of the total nonpolar free energy, which consists of repulsive and attractive components. This novel description of the implicit model improved the agreement of the free energy of association of transmembrane helix dimers in significant amount.